Analysis of emerging contaminants in water and solid samples using high resolution mass spectrometry with a Q Exactive orbital ion trap and estrogenic activity with YES-assay. (January 2017) - Comtois-Marotte, Simon; Chappuis, Thomas; Vo Duy, Sung; Gilbert, Nicolas; Lajeunesse, André; Taktek, Salma; Desrosiers, Mélanie; Veilleux, Éloïse; Sauvé, Sébastien
Abstract: Trace emerging contaminants (ECs) occur in both waste and surface waters that are rich in particulates that have been found to sorb several organic contaminants. An analytical method based on off-line solid-phase extraction (SPE) followed by liquid chromatography-mass spectrometry (LC-MS) analysis was developed for the detection and quantification of 31 ECs from surface water, wastewater, suspended particulate matter (SPM) as well as sediments. Lyophilized sediments and air-dried SPM were subjected to ultrasonic extraction. Water samples and extracts were then concentrated and cleaned-up by off-line SPE. Quantification was realized using a Q Exactive mass spectrometer in both full scan (FS) and MS 2 modes. These two modes were optimized and compared to determine which one was the most suitable for each matrix studied. Yeast estrogen screen assay (YES-assay) adapted from the direct measurement of estrogenic activity without sample extraction was tested on filtered wastewater samples. An endocrine disrupting effect was detected in all effluent samples analyzed with estradiol equivalent concentrations ranging from 4.4 to 720 ng eq E2 L −1 for the WWTP-1 and 6.5–42 ng eq E2 L −1 for the WWTP-2. The analytical methods were also applied on six samples of surface water, the corresponding SPM, the sediments and thirty-nine effluent samples from two wastewater treatment plants (WWTPs) sampled over a period of five months (February to June 2014). Highlights: We analyzed 31 emerging contaminants in water, suspended particulates and sediments. Solid-liquid partitioning coefficient (Kd ) are reported for 12 compounds. No clear relationship observed between chemical measurements and YES assay results.